1972
DOI: 10.1136/jmg.9.3.377
|View full text |Cite
|
Sign up to set email alerts
|

A ring-20 chromosome.

Abstract: . Definitive evidence for the short arm of the Y chromosome associating with the X chromosome during meiosis in the human male. Nature, 226,959-961. Voorhees, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 5 publications
1
83
0
Order By: Relevance
“…Age at onset of seizures varies from infancy to 14 years and is characteristically resistant to treatment (196,198). Although a variety of seizure types were initially reported in single cases, a report by Inoue et al (196) of six cases studied with video-EEG monitoring crystallized a characteristic seizure pattern of repeated nonconvulsive status.…”
Section: Epileptologymentioning
confidence: 99%
See 1 more Smart Citation
“…Age at onset of seizures varies from infancy to 14 years and is characteristically resistant to treatment (196,198). Although a variety of seizure types were initially reported in single cases, a report by Inoue et al (196) of six cases studied with video-EEG monitoring crystallized a characteristic seizure pattern of repeated nonconvulsive status.…”
Section: Epileptologymentioning
confidence: 99%
“…More than 30 cases of epilepsy associated with ring chromosome 20 have been reported (194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207). The locus of fusion between the deleted long and short arms in ring chromosome 20 in 12 cases was one of p13q13, p13q13.3, or p13q13.33.…”
Section: Chromosome 20mentioning
confidence: 99%
“…Abnormalities of chromosome 20 which were identified by Q-and/or G-banding techniques have been reported in complete trisomy 20 (WahlstrSm et al, 1976;Pan et al, 1976), trisomy 20 mosaieism (Pallister et al, 1976), partial trisomy 20p resulting from a transloeation (Krmpotic et al, 1971;Franeke, 1972;Subrt and Bryehn~, 1974;Cohen et aL, 1975, Taylor et al, t976), ring 20 (Atkins et al, 1972;Uchida and Lin, 1972;Faed et al, 1972;Herva et al, 1977), and so far only two reports of a partial deletion 20p have been found (Loiodice et aL, 1970;Kalousek and Therien, 1976), Other structural changes of F group chromosome have been found in bone marrow cells in association with various haematologicat disorders, such as polycythemia vera (Reeves et aL, 1972).…”
Section: Ntroduc T!qnmentioning
confidence: 99%
“…All patients and controls had normal neurologic examinations. Brain magnetic resonance imaging (MRI) results were normal in all patients, and showed brain damage in four controls located in the following areas: right parietal (1), left parietal (1), left occipital (1), and parietooccipital, bilaterally (1).…”
Section: Resultsmentioning
confidence: 99%
“…In the years since the 1972 report from Atkins et al 1 electroencephalography (EEG) studies from patients with ring chromosome 20 epilepsy syndrome have been shown to have a recognizable pattern. EEG typically shows high voltage 3-6 Hz rhythms, with or without spike components, predominantly on frontal areas; during seizures, these rhythms are concomitant with frontal spikes and may spread over the scalp.…”
mentioning
confidence: 99%